Study of the Propagation of the Shock-Air Wave Front in the Axial Air Cavity of a Downhole Charge of Explosives (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In order to increase the efficiency of the explosive impact on the rock and reduce the output of oversize in open pits, it is recommended to increase the pressure and time of the explosion impact on the massif by using an axial air cavity. This paper presents the results of studies of the propagation of the shock-air wave front in the axial air cavity of a borehole explosive charge depending on the detonation velocity, the mass of the explosive charge and the cross-sectional area of the axial cavity. The study of the propagation of the shock-air wave front in the axial air cavity of the borehole explosive charge makes it possible to develop the design of a borehole explosive charge with an axial air cavity, which improves the efficiency of blasting by increasing the duration of the blast wave pulse and reducing the specific consumption of explosives.